ANALISIS PENGARUH SALES GROWTH DAN PROFITABILITAS TERHADAP TAX AVOIDANCE - Kristiani, Vincentia Sekar Ganjur Woro; Rusmita, Sari; Fahmi, Muhammad (ABDI EQUATOR, 2023)
This study aims to determine and examine the effect of sales growth and profitability on tax avoidance. this research uses quantitative methods. The sample used is secondary data in the form of annual reports of industrial sector companies for the period 2017-2021 which comes from the Indonesia Stock Exchange (IDX) website with the sampling technique using purposive sampling method. After selecting a sample based on certain criteria, 15 companies were obtained which will be analyzed with a period of 5 years. The data analysis used in this research is multiple linear regression analysis using data processing program tools in the form of SPSS version 24 and Microsoft Excel 2019. Based on the results of this study, it shows that sales growth has no effect on tax avoidance and profitability has a negative effect on tax avoidance.